1991
DOI: 10.1080/00207239108710615
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in the lagos lagoon sediments

Abstract: Concentrations of cadmium, cobalt, copper, chromium, iron, manganese, nickel, lead and zinc were determined in surface sediments of the Lagos Lagoon, Nigeria. The results revealed largely anthropogenic heavy metal enrichment and implicated urban and industrial wastes and runoff water transporting metals from land-derived wastes, as the sources of the enrichment. Higher levels (F < 0.05) of cadmium, iron, manganese, nickel and zinc occurred in sediment samples collected near industrialized-urban areas than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
1
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 3 publications
(1 reference statement)
6
14
1
1
Order By: Relevance
“…This pattern is in line with the natural distribution these metals in the earth crust. The results obtained for the total concentrations of these metals in the fish sample analysed are generally lower than the results reported by [16][17][18][19][20][21] and higher than results reported by Eletta, et al [22] and conform with result reported by Tukura, et al [23] the…”
Section: Resultssupporting
confidence: 80%
“…This pattern is in line with the natural distribution these metals in the earth crust. The results obtained for the total concentrations of these metals in the fish sample analysed are generally lower than the results reported by [16][17][18][19][20][21] and higher than results reported by Eletta, et al [22] and conform with result reported by Tukura, et al [23] the…”
Section: Resultssupporting
confidence: 80%
“…Their value compares favourably with those of domestic livestock and fish (Dambo, 1993). It is therefore important to determine the levels of metals in these organisms (Okoye, 1991;Paez-Osuna and Ruizx, 1995 (2) Sample collection, preparation and analysis: Grids were marked at each station Periwinkle samples were hand picked at ebb tide fortnightly from the study sites at specific locations. Periwinkles were put into perforated plastic cans with cover, which had been washed with distilled water and left to dry prior to sample collection, and taken to the laboratory.…”
mentioning
confidence: 99%
“…Although pH usually has no direct impact on consumers, it is one of the most important operational water quality parameters. Extremes of pH can affect the palatability of a water but the corrosive effect on distribution systems is a more urgent problem (18).The pH is of the utmost importance in determining the corrositivity of water (16). In general, the lower the value of pH, the higher the level of corrosion.…”
Section: Physicochemical Factors Of Raw and Emf Treated Waste Water Fmentioning
confidence: 99%
“…Organic wastes and other nutrient inputs from sewage and industrial discharges, agricultural and urban runoff can result in decreased oxygen levels. Nutrient input often leads to excessive algal growth; when the algae die, the organic matter is decomposed by bacteria, a process which consumes a great deal of oxygen that could lead to oxygen sag (16). A high DO level in a community water supply is good because it makes drinking water taste better.…”
Section: Physicochemical Factors Of Raw and Emf Treated Waste Water Fmentioning
confidence: 99%
See 1 more Smart Citation